Textural properties of laksa noodle as affected by rice flour particle size - Malahayati, Nura; Syed Muhammad, Sharifah Kharidah; Bakar, Jamilah; Karim, Roselina (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2011)
This study examined the physicochemical properties of rice flours with five different particle sizes (≤63, 80, 100, 125, and 140 μm) prepared by dry milling and their effects on textural properties of laksa noodles. Rice flour with the smallest particle size had the highest water absorption index, peak viscosity, hot paste viscosity, breakdown, final or cold paste viscosity and gel hardness, but the lowest gelatinization temperature. Reduction of rice flour particle size improved textural properties of laksa noodle. Laksa noodle produced from rice flour with the smallest particle size had the best textural properties.